Resettlement patterns: a quantitative and exploratory digital approximation of first-generation Republican exiles who returned to Spain (1939-2010) - Escobar Deras, Mauricio (Hispania Nova, 2021)
This research explores the quantifiable data of 158 first-generation Republican exiles based on the year of repatriation to Spain (from 1939 to 2010); and their resettlement choices once in the country. The data was obtained from the merging of two ad hoc databases; queried to see if the individuals returned to their birthplace after their exile period or if they chose a larger or smaller city to re-incorporate into Spanish society. Gender differences are moderately examined to explore variances between women favoring their birth cities and men’s movement away from their hometowns due to external forces. We reached a series of conclusions that can be tentatively applied to the greater return experience and correlated a strong link between time spent in exile and the likelihood; or lack thereof; of returning to the city of origin. In so doing; helping to discern the adaption back into Spanish society.
Keywords: return; repatriation; republican exile; digital humanities; women